From the lungs to the kidneys; a case of renal AA amyloidosis in a patient with pulmonary TB - Yesid Fabián Mantilla-Flórez; Eduardo Tuta-Quintero; Carlos Mauricio Calderón-Vargas; Paula Violeta Rodríguez-Segura; Nicolas Díaz-Pinilla (Society of Diabetic Nephropathy Prevention, 2021)
AA amyloidosis is a complication related to several chronic inflammatory conditions like cancer, autoimmune diseases and infections, among others. The disease implicates amyloid fibrils deposit in tissues leading to organ failure. Renal involvement has been closely associated with amyloidosis and sometimes with tuberculosis too. Therefore, it is important to achieve a renal biopsy that allows elucidating the etiology of the clinical picture in order to provide the correct treatment to the patients. In this paper, we present a case of renal amyloidosis secondary to pulmonary tuberculosis which debuted as nephrotic syndrome.